Prefrontal Cortex Activity During Walking: Effects of Aging and Associations With Gait and Executive Function - Nóbrega-Sousa, Priscila [UNESP] (2020)
Background: Declines in gait parameters are common with aging and more pronounced in tasks with increased executive demand. However, the neural correlates of age-related gait impairments are not fully understood yet. Objectives: To investigate (a) the effects of aging on prefrontal cortex (PFC) activity and gait parameters during usual walking, obstacle crossing and dual-task walking and (b) the association between PFC activity and measures of gait and executive function. Methods: Eighty-eight healthy individuals were distributed into 6 age-groups: 20-25 (G20), 30-35 (G30), 40-45 (G40), 50-55 (G50), 60-65 (G60), and 70-75 years (G70). Participants walked overground under 3 conditions: usual walking, obstacle crossing, and dual-task walking. Changes in oxygenated and deoxygenated hemoglobin in the PFC were recorded using functional near-infrared spectroscopy. Gait spatiotemporal parameters were assessed using an electronic walkway. Executive function was assessed through validated tests. Results: Between-group differences on PFC activity were observed for all conditions. Multiple groups (ie, G30, G50, G60, and G70) showed increased PFC activity in at least one of the walking conditions. Young adults (G20 and G30) had the lowest levels of PFC activity while G60 had the highest levels. Only G70 showed reduced executive function and gait impairments (which were more pronounced during obstacle crossing and dual-task walking). PFC activity was related to gait and executive function. Conclusions: Aging causes a gradual increase in PFC activity during walking. This compensatory mechanism may reach the resource ceiling in the 70s, when reduced executive function limits its efficiency and gait impairments are observed.